Providing a model of emotional and rational appeals in video marketing based on social networks - Moohan Mohammadi; payam paslari; saeed moradpour; sadegh masjoodi (ارزش آفرینی در مدیریت کسب و کار)
AbstractThe aim of the current research is to provide a model of emotional and rational appeals in video marketing based on social networks. According to its purpose, the research method is applicable, and descriptive in terms of data collection. The statistical population of the research includes 200 male and female students between the ages of 25 and 35, selected as a sample and exposed to two types of short-term video advertisement stimuli. The sampling method is random. Data was collected through a questionnaire. SPSS and PLS software were used in data analysis. In this study, through the structural equation approach, it was determined that there is a significant difference between emotional and rational appeals in "attracting" the attention of the audience to video advertisements, which depends on the type and intensity of the emotional or rational load used in content production, which have different effect in creating "behavioral conflict" in the target audience. Also, the effect of the attention-attracting variable was identified as a mediating variable in creating behavioral engagement.Extended Abstract                                           IntroductionVideo marketing or what is known as "Video Marketing" has occupied a major and important part of the world of content marketing and, accordingly, digital marketing (Stringfellow, 2017), and for this reason, it has attracted the attention of many researchers. The emergence of the Internet, as the top technology of the 80s, has significantly affected marketing and its sub-branches, especially video marketing (Sheldon, 2013), and one of these effects is the intersection of video marketing and social networks or Social Media (Luo et al, 2013).Social media, which are equivalent to the term social networks in this study, are one of the most important known components that increasingly involve almost all aspects of human life, from education to business (Alalwan et al, 2017); despite the differences that Wikipedia has made between the network and social media (Bennett, 2013).Many things have been mentioned about the importance of the impact of social media on marketing; for example, it has been stated that if the customer cannot first get help from the information available on social media to make a decision, then in the second step, he will go to search engines, and this shows the position of social media in the behavior leading to customer purchase (Jameel, 2023). For this reason, the function of various types of emotional and rational appeals as two key parameters in the effectiveness of video marketing in social networks will be the subject of this study, and we will try to find the answer to the question: Is there any significant difference between emotional and rational appeals in the effectiveness of video marketing or not?Theoretical FrameworkAttention in video marketing"Attracting attention" is so important that researchers consider the goal of video marketing only to attract the attention of the audience and change his decision to continue watching (Arantes et al, 2018), and consider it as the main factor of competition in this type of marketing (Sheldon, 2013). For this reason, in this research, attracting attention was considered as the beginning of the process of creating effectiveness in video marketing.Emotional and intellectual appealsSeveral factors have been introduced in marketing as the factor to attract the attention of the audience, among which the role of emotional appeals can be mentioned as an important factor in attention (Melin, 2014). Excitement is one of the necessary elements to achieve attention in video marketing in such a way that "The customer's decision-making journey in video marketing begins with a video ad" (Maenhout, 2023), and only does positive emotions that affect the audience's attention, but negative stimuli also play an important role in attracting the viewer's attention (Vaish et al, 2008) (Rozin & Royzman, 2001).The engagementCrane & Sornette (2008) were the first people who introduced the term "engagement" in today's sense as a valuable tool for measuring the effectiveness of video marketing, in their definition: "audience engagement in video is a chance to share video and increase the number of visits" (Crane & Sornette, 2008).Dong et al, (2023) investigated the four main factors of short branded video content (content matching, informational relevance, storytelling, and emotionality), customer engagement (likes, comments, and shares) as well as the moderating effect of publication time (morning). The experimental results show that the content characteristics of short videos significantly affect consumer engagement. In addition, the time of release of videos significantly moderated the relationship between emotionality of short videos and consumer engagement. Content posted in the morning increased the positive effect of warmth, excitement, and happiness on consumer engagement compared to content posted in the afternoon. The practical implications of the findings provide new insights for the dissemination of products and brand culture through short videos. The authors suggest that companies using brand videos consider content matching, informational relevance, storytelling, and emotionality in their design. Authenticity/value from a broader perspective; this study develops a new method to comprehensively evaluate short-brand video content based on four dimensions (content matching, informational relevance, storytelling, and emotional), examines and the value of these dimensions to create social media marketing.Hosseini (2023) investigated the impact of video marketing and its various strategies on consumer behavior. The results showed that the experience of video marketing strategies does not have a significant effect on the behavior of Ramak dairy products consumers. Also, brand identity, advertising, usefulness of information, and service quality of video marketing strategies have a significant effect on the behavior of consumers of dairy products of the studied company. After presenting the results, suggestions and strategies are presented in the field of findings related to the research.Research methodologyThe research method is applicable in terms of purpose, and descriptive in terms of data collection. The statistical population of the research includes 200 male and female students between the ages of 25 and 35, selected as a sample and exposed to two types of short-term video advertisement stimuli. The sampling method is random. Data was collected through a questionnaire.Research findingsSPSS and PLS software were used in data analysis. In this study, through the structural equation approach, it was determined that there is a significant difference between emotional and rational appeals in "attracting" the attention of the audience to video advertisements, which depends on the type and intensity of the emotional or rational load used in content production, which have different effect in creating "behavioral conflict" in the target audience. Also, the effect of the attention-attracting variable was identified as a mediating variable in creating behavioral engagement.ConclusionThe present research was conducted with the aim of presenting the model of emotional and rational appeals in video marketing based on social networks with the approach of structural equations. The results of this research is aligned with the results of Dong et al, (2023), Asgharzadeh et al, (2023), Hosseini (2023), Zhuang (2022), Yazdani Kachuei et al, (2022), Taleghani et al, (2022), Sasanpour & Amini Lari (2021), Song et al, (2021), and Casais & Pereira (2021). Zhuang (2022) showed that screen mode, subtitles, and video title length significantly affect consumer engagement by influencing the central information processing pathway; and music and narration positively influence consumer engagement by functioning in the peripheral information processing pathway. This study contributes to the social media marketing and consumer engagement literature by uncovering the influencers for consumer engagement in the context of a brand's short-form video. More importantly, this study provides practical tactics for brands to create compelling videos to attract engagement and achieve marketing goals.Thus, based on the findings of this study, it is suggested:Firstly, to increase the effectiveness of video marketing programs, one should always be optimistic about the use of emotional appeals, although this appeal has a special relationship with many other factors, including demographics.Secondly, although the use of emotional appeals is considered to be a kind of anchor and support point for the effectiveness of video advertisements, the abilities of rational appeals should not be neglected.